The role of molecular markers in breeding for qualitative and quantitative traits of common bean - Kelly, James D.; Miklas, Phillip N. (International Center for Tropical Agriculture, 1997)
Improving selection efficiency through indirect selection is an attractive alternative to plant breeders working to improve qualitative and quantitative traits of common bean (Phaseolus vulgaris L). For the successful application of indirect selection, tight linkages must be developed between simple selectable genetic markers and an economically important gene or quantitative trait loci (QTL) controlling a complex trait. Although indirect selection for qualitative traits appears most promising, direct selection for major gene traits may in certain cases be easier, faster and more cost effective. However, indirect selection of race-specific disease resistance genes offers breeders a viable alternative to ensure that favorable gene combinations are present in new cultivars. Simplifying the selection of complex traits using QTL analysis with linked markers would permit selection in the absence of the pathogen or in locations where trait expression is variable. Combining different mechanisms for resistance is only possible using markers when the phenotypic expression is similar after disease inoculation. Random amplified polymorphic DNA (RAPD) markers tightly linked to individual race-specific resistance genes forms the basis for effective indirect selection for durable genetic resistance. Over 30 RAPD markers linked to 17 major genes which condition resistance to four pathogens of common bean nave been found. In addition, markers associated with QTL conditioning resistance to the three diseases (bean golden mosaic virus, common bacterial blight and web blight) of major importance in the tropics have been identified. These tightly linked RAPD markers have potential to facilitate the efficient selection of complex traits and pyramiding of epistemic resistance genes against different pathogens of common bean. Limitations to marker-assisted selection and the value of genetic mapping and QTL analysis in improving the efficiency of bean breeding programs are discussed.